The Mystery of the Multiplying Marks: A Modification of the Monetary Model - Frankel, Jeffrey A. (The Review of Economics and Statistics, 1982)
Fair, Ray, and Dwight Jaffee, of for Markets in Disequilibrium, Econometrica 40 (May 1972), 497-514. Fair, Ray, and Harry Kelejian, of for Markets in Disequilibrium: Further Study, Econometrica 42 (Jan. 1974), 177-190. Goldfeld, Stephen, and Richard Quandt, Estimation in a Disequilibrium Model and the Value of Information, Journal of Econometrics 3 (Nov. 1975), 325-348. Hausman, Jerry, Effects of Wages, Taxes, and Fixed Costs on Women's Force Participation, Journal of Public Economics 14 (Oct. 1980), 161-194. McDonald, John, and Robert Moffitt, Uses of Tobit Analysis, this REVIEW 62 (May 1980), 318-321. Maddala, G. S., and Forrest Nelson, Maximum Likelihood Methods for Models of Markets in Disequilibrium, Econometrica 42 (Nov. 1974), 1013-1030. Moffit, Robert, and Kenneth Kehrer, Effect of Tax and Transfer Programs on Supply: The Evidence from the Income Maintenance Experiments, in Ronald Ehrenberg (ed.), Research in Economics, Vol. 4 (Greenwich, Conn.: JAI Press, 1981). Nelson, Forrest, Censored Regression Models with Unobserved, Stochastic Censoring Thresholds, Journal of Econometrics 6 (Nov. 1977), 309-327. Oi, Walter, Labor as a Quasi-Fixed Factor, Journal of Political Economy 70 (Dec. 1962), 538-555. Rosen, Harvey, and Richard Quandt, Estimation of a Disequilibrium Aggregate Market, this REVIEW 60 (Aug. 1978), 371-379. Tobin, James, Estimation of Relationships for Limited Dependent Variables, Econometrica 26 (Jan. 1958), 24-36.